Total Synthesis of Syringolin A and Improvement of Its Biological Activity. (25th March 2014) - Chiba, Takuya; Hosono, Hidetaka; Nakagawa, Koji; Asaka, Masahiro; Takeda, Hiroshi; Matsuda, Akira; Ichikawa, Satoshi
Abstract The development process for syringolin A analogues having improved proteasome inhibitory and antitumor activity is described. The strategy was to first establish a convergent synthesis of syringolin A using a rare intramolecular Ugi three‐component reaction in the last stage of the synthesis, so as to gain access toa set of structure‐based analogues. The inhibitory activity of chymotrypsin‐like activity of 20S proteasome was largely improved by targeting the S3 subsite of the β5 subunit. Cytotoxic activity was also improved by installing the membrane‐permeable substituent. These biological properties are comparable to those of bortezomib, a clinically used first‐line proteasome inhibitor.